2014
DOI: 10.1017/jfm.2014.210
|View full text |Cite
|
Sign up to set email alerts
|

Granular jet impact: probing the ideal fluid description

Abstract: We investigate the impact of a granular jet on a finite target by means of particle simulations. The resulting hydrodynamic fields are compared with theoretical predictions for the corresponding flow of an incompressible and rotation-free fluid. The degree of coincidence between the field obtained from the discrete granular system and the idealized continuous fluid flow depends on the characteristics of the granular system, such as granularity, packing fraction, inelasticity of collisions, friction and target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…4), while the formula (6) deviates from the simulation results when V * ≡ V m/k n /d is larger than 0.3. This result is interesting because the perfect fluidity observed in granular jets or granular fluids (Cheng et al 2007;Ellowitz et al 2013;Müller et al 2014;Blumenfeld et al 2010) is quantitatively verified in our setup, at least, for relatively slow flows and moderate dense granular medium. We should note that our problem can be converted into a jet problem for a circular target, if we use the frame of the stationary tracer.…”
Section: System Without Dry Frictionsupporting
confidence: 73%
“…4), while the formula (6) deviates from the simulation results when V * ≡ V m/k n /d is larger than 0.3. This result is interesting because the perfect fluidity observed in granular jets or granular fluids (Cheng et al 2007;Ellowitz et al 2013;Müller et al 2014;Blumenfeld et al 2010) is quantitatively verified in our setup, at least, for relatively slow flows and moderate dense granular medium. We should note that our problem can be converted into a jet problem for a circular target, if we use the frame of the stationary tracer.…”
Section: System Without Dry Frictionsupporting
confidence: 73%
“…Considering the fact that the particle is about 2000 times the momentum of air at identical velocity in atmospheric pressure, and the gas may be neglected for dense granular impinging jets. This strategy used was the same to several previous DEM works on granular jets impinging on a solid target …”
Section: Resultsmentioning
confidence: 99%
“…Regarding impacts against fixed targets, previous workers showed granular and high speed liquid jets astoundingly both produce quite similar coherent ejecta sheets [5][6][7]. Because the flow from a high speed liquid impinging a fixed target is similar to a perfect fluid, this led to a discussion of whether or not a granular jet impact against a target behaves like a perfect fluid [7][8][9][10][11]. Despite the similar ejecta from the target impacts, it was later shown that granular jet impact against a target produces a large, stagnant dead-zone, and that furthermore inserting large dead-zone-like structures into perfect fluids barely affected the ejecta [12].…”
Section: Introductionmentioning
confidence: 99%